Identification of Proteins Sensitive to Thermal Stress in Human Neuroblastoma and Glioma Cell Lines - Xu, Guilian; Stevens, Jr, Stanley M.; Kobiessy, Firas; Brown, Hilda; McClung, Scott; Gold, Mark S.; Borchelt, David R. (PLOS ONE, 2012)
Heat-shock is an acute insult to the mammalian proteome. The sudden elevation in temperature has far-reaching effects on protein metabolism, leads to a rapid inhibition of most protein synthesis, and the induction of protein chaperones. Using heat-shock in cells of neuronal (SH-SY5Y) and glial (CCF-STTG1) lineage, in conjunction with detergent extraction and sedimentation followed by LC-MS/MS proteomic approaches, we sought to identify human proteins that lose solubility upon heat-shock. The two cell lines showed largely overlapping profiles of proteins detected by LC-MS/MS. We identified 58 proteins in detergent insoluble fractions as losing solubility in after heat shock; 10 were common between the 2 cell lines. A subset of the proteins identified by LC-MS/MS was validated by immunoblotting of similarly prepared fractions. Ultimately, we were able to definitively identify 3 proteins as putatively metastable neural proteins; FEN1, CDK1, and TDP-43. We also determined that after heat-shock these cells accumulate insoluble polyubiquitin chains largely linked via lysine 48 (K-48) residues. Collectively, this study identifies human neural proteins that lose solubility upon heat-shock. These proteins may represent components of the human proteome that are vulnerable to misfolding in settings of proteostasis stress.